Commercial formulations of Bacillus spp. for sugarcane pineapple disease control and growth promotion - Brandi, Fabio [UNESP]; Heck, Daniel Winter [UNESP]; Ferreira, Thiago Costa [UNESP]; Bettiol, Wagner (Empresa Brasil Pesq Agropec, 2018)
The objective of this work was to evaluate the commercial formulations of Bacillus subtilis QST-713 and Bacillus pumilus QST-2808 on mycelial growth inhibition of Thielaviopsis paradoxa, for the control of the pineapple disease and growth promotion in sugarcane. The inhibition of mycelial growth was evaluated in paired culture tests. Bacillus isolates were transferred to Petri dishes 48 hours before the pathogen, and the zone of inhibition was determined. The direct effect of the autoclaved commercial formulations at 0, 0.001, 0.01, 0.1, 1.0, and 10.0% on the inhibition of pathogen mycelial growth was evaluated. Bacillus spp. potential in controlling the disease and promoting plant growth was evaluated in assays on plant development and disease severity, both under controlled conditions and in the field. Bacillus isolates inhibited pathogen mycelial growth; however, the isolates did not control the disease effectively in the growth chamber and in the field. In the field assay without infestation by the pathogen, all treatments with biocontrol agents and fungicide increased the yield of cane stalks and sugar per hectare, compared with the control. In the assay with infestation by the pathogen, the B. pumilus-based product (2.0 L ha(-1)) and fungicide differed from the control only for the variable number of tillers.
Keywords: Saccharum; Thielaviopsis paradoxa; alternative control; biological control